2021
DOI: 10.1155/2021/6645336
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Deworming Drugs and Its Individual and Community Level Predictors among Pregnant Married Women in Cameroon: A Multilevel Modeling

Abstract: Background. Although deworming pregnant women is one of the strategies to reduce parasites (roundworms and hookworms) causing anemia and related perinatal and maternal complications, utilization of deworming medication among pregnant women in Cameroon is suboptimal. Comprehensive assessment of individual, household (including women’s autonomy), and community-level factors associated with utilization of deworming medication has not been done so far. Therefore, we investigated the individual/household and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
5
11
1
Order By: Relevance
“…Also, pregnant women who had ANC had a higher likelihood of taking deworming medication than pregnant women who did not have ANC. This finding is in line with a study done in Cameroon [ 34 ]. This may be due to the fact that ANC visit creates a good opportunity to receive deworming medication and more information about benefits of deworming and positive pregnancy outcomes are gained through counseling during repeated ANC visit [ 24 ], and WHO recommended to routinely provide deworming medication during ANC visit [ 22 , 24 ], hence a women with ANC visit can easily access the medication and utilize it.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Also, pregnant women who had ANC had a higher likelihood of taking deworming medication than pregnant women who did not have ANC. This finding is in line with a study done in Cameroon [ 34 ]. This may be due to the fact that ANC visit creates a good opportunity to receive deworming medication and more information about benefits of deworming and positive pregnancy outcomes are gained through counseling during repeated ANC visit [ 24 ], and WHO recommended to routinely provide deworming medication during ANC visit [ 22 , 24 ], hence a women with ANC visit can easily access the medication and utilize it.…”
Section: Discussionsupporting
confidence: 94%
“…From our result the utilization of deworming among pregnant women was only 5.69% [5.24%, 6.33] which is very low which directly contributes for the high level helminthic infection among pregnant women in Ethiopia. This result is lower than a study conducted in Tanzania (60.1%) [25], Cameroon(29.8%) [34] and 23% in 49 STH endemic countries [33]. The variations across different countries might be related to factors associated with usage of deworming medication such as socioeconomic factors, difference in study settings, and difference in health care service access and utilization [5,34].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this study, women who attended primary and above primary educational status were more likely to take their child deworming medication as compared to uneducated mothers. This is in line with studies in Cameron [ 18 ], and Ghana [ 19 ] which show educated mothers were more utilizing deworming medication for their child and themselves. This is because of that, the educated mother has health advantages and better essence of health inputs such as dewormed to the health of children relative to the uneducated partners [ 19 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…But its implementation was low [ 16 ]. Studies showed that factors such as; maternal media exposure status [ 1 , 12 , 16 , 17 ], maternal control of household healthcare decisions [ 16 ], child vitamin-A supplementation [ 16 ], having a history of diarrheal disease [ 16 ], maternal and paternal education [ 16 , 18 , 19 ], and child age [ 12 ] were significant predictors of deworming supplements.…”
Section: Introductionmentioning
confidence: 99%